Influence of preformed antibody on the pathogenesis of experimental Candida albicans endocarditis. - Scheld, W M (1983)
The influence of preformed antibody on the induction of experimental Candida albicans endocarditis was investigated by both in vitro and in vivo techniques. Preincubation of C. albicans with immune serum (raised in rabbits by intravenous injection of Formalin-killed yeast cells) decreased adhesion to the constituents of nonbacterial thrombotic endocarditis, e.g., fibrin plus platelets, in vitro. Two different methods, with radiolabeled or viable yeast cells, were confirmatory and demonstrated decreased adhesion of immune serum-treated C. albicans cells to 0 to 7.8% of control values (P less than 0.001). These results correlated with protection from the development of C. albicans endocarditis in the immunized rabbits. The mean (+/- standard deviation) infectious dose for 50% of the animals was 10(5.29) +/- 10(0.07) in 48 control animals versus 10(7.11) +/- 10(0.22) in 37 immunized rabbits (P less than 0.001). These studies suggest that humoral antibody may protect against C. albicans endocarditis, perhaps through inhibition of adhesion, a crucial early step in the pathogenesis of endocarditis.